Dexamethasone application for in vitro fertilisation in non-classic 17-hydroxylase/17,20-lyase-deficient women - Yang, Xiu-Li; Zhang, Ting-Ting; Shang, Jing; Xue, Qing; Kuai, Yan-Rong; Wang, Sheng; Xu, Yang (Frontiers in Endocrinology, 2022)
Context High progesterone levels in the follicular stage interfere with the implantation window, causing infertility in women with 17-hydroxylase/17,20-lyase deficiency (17OHD). Dexamethasone can restore cortisol deficiency and suppress inappropriate mineralocorticoid secretion to control hypertension in 17OHD patients, but poses risks to the foetus if administered during pregnancy. Objective We prospectively explored a rational glucocorticoid use protocol for assistive reproduction in a woman with non-classic 17OHD that reduced glucocorticoid side effects. Method In this study, the treatment protocol for this 17OHD patient included the following steps. First, the appropriate type and dose of glucocorticoid for endogenous progesterone suppression was determined. Then, glucocorticoid was discontinued to increase endogenous progesterone levels for ovarian stimulation. Next, dexamethasone plus GnRHa were used to reduce progesterone levels in frozen embryos for transfer. Once pregnancy was confirmed, dexamethasone was discontinued until delivery. Results Dexamethasone, but not hydrocortisone, reduced progesterone levels in the 17OHD woman. After endogenous progesterone-primed ovarian stimulation, 11 oocytes were retrieved. Seven oocytes were 2PN fertilised and four day-3 and two day-5 embryos were cryopreserved. After administering dexamethasone plus gonadotropin-releasing hormone agonist (GnRHa) to reduce progesterone levels to normal, hormone replacement therapy was administered until the endometrial width reached 9 mm. Exogenous progesterone (60 mg/day) was used for endometrial preparation. Two thawed embryos were transferred on day 4. Dexamethasone was continued until pregnancy confirmation on the 13th day post-transfer. Two healthy boys, weighing 2100 and 2000 g, were delivered at 36 weeks’ gestation. Conclusion Rational use of dexamethasone synchronised embryonic development with the endometrial implantation window, while not using in post-implantation avoided its side effects and promoted healthy live births in women non-classic 17OHD undergoing in vitro fertilisation.